Pemberdayaan Masyarakat untuk Pengendalian Penyakit Ayam dan Mencegah Penyebaran Avian Influenza di Desa Oenaek - Marni Marni; Ribka Limbu; Hery Leo Sianturi (Yayasan Sumber Daya Manusia Cerdas, 2024)
step towards increasing national food security, reducing economic losses on livestock, and maintaining human health. This Community Service seeks to improve community welfare by strengthening chicken breeder organizations. Empowerment is carried out through training and demonstrations of chicken farming technology, as well as increasing community support and collaboration with chicken breeder organizations in the two villages. The implementation strategy is participatory in nature which includes discussion activities and exchange of ideas between groups of chicken farmers, as well as the use of the internet and social media to increase knowledge. The findings show that training and demonstration of chicken farming technology is very useful in increasing the skills and knowledge of chicken farmer groups in solving difficulties such as dealing with chicken diseases and fighting Avian Influenza. After the implementation of the chicken farmer group empowerment initiative, community support and collaboration for chicken farmer groups in Oenaek Village has increased. It is important to expand the frequency and intensity of training and demonstrations of chicken farming technology, as well as collaboration between chicken farmer organizations in Oenaek Village. Apart from that, the use of the internet and social media as a way to increase knowledge can be used to achieve greater goals. This is expected to increase production and quality of chicken farming, as well as reduce the risk of disease transmission in Oenaek Village.